Continuous home cage monitoring of activity and sleep in mice during repeated paroxetine treatment and discontinuation - Helen M. Collins; Raquel Pinacho; S. K. Eric Tam; Trevor Sharp; David M. Bannerman; Stuart N. Peirson (Psychopharmacology, 2023)
Rationale Non-invasive home cage monitoring is emerging as a valuable tool to assess the effects of experimental interventions on mouse behaviour. A field in which these techniques may prove useful is the study of repeated selective serotonin reuptake inhibitor (SSRI) treatment and discontinuation. SSRI discontinuation syndrome is an under-researched condition that includes the emergence of sleep disturbances following treatment cessation. Objectives We used passive infrared (PIR) monitoring to investigate changes in activity, sleep, and circadian rhythms during repeated treatment with the SSRI paroxetine and its discontinuation in mice. Methods Male mice received paroxetine (10 mg/kg/day, s.c. ) for 12 days, then were swapped to saline injections for a 13 day discontinuation period and compared to mice that received saline injections throughout. Mice were continuously tracked using the Continuous Open Mouse Phenotyping of Activity and Sleep Status (COMPASS) system. Results Repeated paroxetine treatment reduced activity and increased behaviourally-defined sleep in the dark phase. These effects recovered to saline-control levels within 24 h of paroxetine cessation, yet there was also evidence of a lengthening of sleep bouts in the dark phase for up to a week following discontinuation. Conclusions This study provides the first example of how continuous non-invasive home cage monitoring can be used to detect objective behavioural changes in activity and sleep during and after drug treatment in mice. These data suggest that effects of paroxetine administration reversed soon after its discontinuation but identified an emergent change in sleep bout duration, which could be used as a biomarker in future preclinical studies to prevent or minimise SSRI discontinuation symptoms.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Pharmacological evidence that 5-HT2C receptor blockade selectively improves decision making when rewards are paired with audiovisual cues in a rat gambling task - Wendy K. Adams; Chris Barkus; Jacqueline-Marie N. Ferland; Trevor Sharp; Catharine A. Winstanley (Psychopharmacology, 2017)

Fornix deep brain stimulation enhances acetylcholine levels in the hippocampus - Sarah Hescham; Ali Jahanshahi; Judith V. Schweimer; Stephen N. Mitchell; Guy Carter; Arjan Blokland; Trevor Sharp; Yasin Temel (Brain Structure and Function, 2016)

Effects of the potential lithium-mimetic, ebselen, on impulsivity and emotional processing - Charles Masaki; Ann L. Sharpley; Charlotte M. Cooper; Beata R. Godlewska; Nisha Singh; Sridhar R. Vasudevan; Catherine J. Harmer; Grant C. Churchill; Trevor Sharp; Robert D. Rogers; Philip J. Cowen (Psychopharmacology, 2016)

Retrospective stable isotope analysis reveals ecosystem responses to river regulation over the last century - Thomas F. Turner; Trevor J. Krabbenhoft; Michael L. Collyer; Corey A. Krabbenhoft; Melanie S. Edwards; Zachary D. Sharp (Ecology, 2015)
Disruption of natural flow regimes, nutrient pollution, and other consequences of human population growth and development have impacted most major rivers of the world. Alarming losses of aquatic biodiversity coincide with human‐caused river alteration, but effects of biotic homogenization on aquatic ecosystem processes are not as well documented. This is because unaltered systems for comparison are scarce, and some ecosystem‐wide effects may take decades to manifest. We evaluated aquatic ecosystem responses to extensive river‐floodplain engineering and nutrient addition in the Rio Grande of southwestern North America as revealed by changes in trophic structure of, and resource availability to, the fish community. Stable Isotope Analysis (SIA) was conducted on museum‐preserved fishes collected over a 70‐year period of intensive river management and exponential human population growth. Trophic complexity and resource heterogeneity for fish consumers (measured as “isotopic niche breadth”) decreased following sediment deprivation and channelization, and these effects persist into the present. Increased nutrient inputs led to δ 15 N enrichment in the entire fish community at all affected sites, and a shift to autochthonous sources of carbon at the most proximal site downstream of wastewater release, probably via bottom‐up transfer. Overall, retrospective SIA of apex consumers suggests radical change and functional impairment of a floodplain river ecosystem already marked by significant biodiversity loss.

Activation of 5-HT6 receptors facilitates attentional set shifting - Katherine E. Burnham; Mark G. Baxter; John R. Bainton; Eric Southam; Lee A. Dawson; David M. Bannerman; Trevor Sharp (Psychopharmacology, 2010)

S32006, a novel 5-HT2C receptor antagonist displaying broad-based antidepressant and anxiolytic properties in rodent models - Anne Dekeyne; Clotilde Mannoury la Cour; Alain Gobert; Mauricette Brocco; Françoise Lejeune; Florence Serres; Trevor Sharp; Annie Daszuta; Amélie Soumier; Mariusz Papp; Jean-Michel Rivet; Gunnar Flik; et al. (Psychopharmacology, 2008)

Simultaneous blockade of 5-HT1A/B receptors and 5-HT transporters results in acute increases in extracellular 5-HT in both rats and guinea pigs: in vivo characterization of the novel 5-HT1A/B receptor antagonist/5-HT transport inhibitor SB-649915-B - Zoë A. Hughes; Kathryn R. Starr; Claire M. Scott; Michael J. Newson; Trevor Sharp; Jeannette M. Watson; Jim J. Hagan; Lee A. Dawson (Psychopharmacology, 2007)

Interaction of the novel antipsychotic aripiprazole with 5-HT1A and 5-HT2A receptors: functional receptor-binding and in vivo electrophysiological studies - Arlene D. Stark; Shaun Jordan; Kelly A. Allers; Robert L. Bertekap; Ruoyan Chen; Tanaz Mistry Kannan; Thaddeus F. Molski; Frank D. Yocca; Trevor Sharp; Tetsuro Kikuchi; Kevin D. Burris (Psychopharmacology, 2007)

Fos immunocytochemical studies on the neuroanatomical sites of action of acute tyrosine depletion in the rat brain - Marisa Le Masurier; Philip J. Cowen; Trevor Sharp (Psychopharmacology, 2004)